The Market for Conservation and Other Hostages - Bård Harstad (Center for Economic Studies and ifo Institute (CESifo), 2013)
A conservation good (such as a tropical forest) is owned by a seller who is tempted to consume (or cut), but a buyer benefits more from conservation. The seller does conserve if the buyer is expected to buy, but the buyer is unwilling to pay as long as the seller conserves. This contradiction implies that the market for conservation cannot be efficient and conservation is likely to fail. A leasing market is inefficient for similar reasons and dominates the sales market if and only if the conservation value is low, the consumption value high, and the buyer's protection cost large. The theory explains why optimal conservation often fails and why conservation abroad is leased, while domestic conservation is bought.
Keywords: Q30; Q23; D78; D62; H87; 330; conservation; deforestation; dynamic games; sales v rental markets